2020
DOI: 10.1016/s0140-6736(20)30608-5
|View full text |Cite
|
Sign up to set email alerts
|

Health sector spending and spending on HIV/AIDS, tuberculosis, and malaria, and development assistance for health: progress towards Sustainable Development Goal 3

Abstract: Background Sustainable Development Goal (SDG) 3 aims to "ensure healthy lives and promote well-being for all at all ages". While a substantial effort has been made to quantify progress towards SDG3, less research has focused on tracking spending towards this goal. We used spending estimates to measure progress in financing the priority areas of SDG3, examine the association between outcomes and financing, and identify where resource gains are most needed to achieve the SDG3 indicators for which data are availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 31 publications
3
73
0
Order By: Relevance
“…Malaria and dengue are the most common mosquito-borne diseases in humans, with an estimated 212 million cases and 96 million cases reported respectively each year [ 5 ]. Annually, dengue illness costs approximately US$9 billion [ 6 ], whereas malaria spending is approximately US$5 billion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria and dengue are the most common mosquito-borne diseases in humans, with an estimated 212 million cases and 96 million cases reported respectively each year [ 5 ]. Annually, dengue illness costs approximately US$9 billion [ 6 ], whereas malaria spending is approximately US$5 billion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being considerably behind LMIC in economic development and health spending, LIC+ achieved significantly better vaccination coverage as a group. Other studies have also observed that higher spending does not always results in improved health services or outcomes 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Significant research has been conducted in spatio-temporal analysis for multiple domains including sociology, criminology, economics, biology, health and environmental sciences etc. [37][38][39][40][41][42][43][44]. In the context of health data clustering, using the above-mentioned mechanisms can greatly affect the resulting clusters since the process of clustering is sensitive to space and time scales [45].…”
Section: Related Workmentioning
confidence: 99%